Determinants of Teacher’s Continuance Intention to Adopt Virtual Learning Environment in Malaysian Schools - Luqman Hakim, Satiman; Nadiatulhuda, Zulkifli (International Federation of Engineering Education Societies (IFEES), 2022)
The adoption of virtual learning environment (VLE) has started to gain serious attention worldwide including Malaysia, where its usage during the Covid-19 pandemic outbreak in particular has become a necessity. Nevertheless, the extent to which teachers have adopted the VLE and which factors are most influencing the continued intention to adopt VLE post pandemic remain ambigious. The objective of this conceptual study is to provide a conceptual framework in investigating the factors that most influence the continued intention to adopt VLE among teacher in Malaysian school. This study overview several important variables that may influence the continued intention to adopt VLE from three contexts (technology, organization and environment) which include relative advantage, compatibility. observability, technological infrastructure, school support, technical support and government support. Finally, this study can improve the understanding about which factors that may encourage or hinder the continued intention to adopt VLE in Malaysian school to enhance education quality for societal change.